Reliability study of high brightness leds under high frequency switching current and thermal cycling condition - Wang, Kai (2014)
With the development in Visible Light Communication (VLC), and LED is a key component in that system, study the reliability of LED under power cycling and thermal cycling becomes a popular project around the world.